Neutron rate estimates in MAST based on gyro-orbit modelling of fast ions. (10th December 2020) - Sperduti, A.; Cecconello, M.; Conroy, S.; Snicker, A.
Abstract: A discrepancy between predicted and measured neutron rates on MAST using TRANSP/NUBEAM has previously been observed and a correction factor of about 0.6 was needed to match the two: this correction factor could not be accounted for by the experimental uncertainties in the plasma kinetic profiles nor in the NBI energy and power (Cecconello et al 2019 Nucl. Fusion 59 016006). Further causes of this discrepancy are here studied by means of TRANSP/NUBEAM and ASCOT/BBNBI simulations. Different equilibria, toroidal field ripples, uncertainties on the NBI divergence value and gyro-orbit effects were studied and simulations were performed with both transport codes. It was found that the first three effects accounted for only a 5% variation in the fast ion density. On the other hand, full gyro-orbit simulations of the fast ions dynamics carried out in ASCOT/BBNBI resulted in an approximately 20% reduction of the fast ion population compared to TRANSP/NUBEAM. A detailed analysis of the fast ion distributions showed how the drop occurred regardless of the energy at pitch values ⩽−0.4. The DRESS code was then used to calculate the neutron rate at the neutron camera detector's location showing that the discrepancy is considerably reduced when the full gyro-orbit fast ion distribution is used, with now the correction factor, used to match experimental and predicted neutron rates, being around 0.9.